Effect of Compaction for Marine Clay and Pressmud to Enhanced Clay Liner Efficiency - Abdul Rahman Abdul Samad; Safingi Shafizah; Sidek Norbaya; Arshad Mohd Fadzil (E3S Web of Conferences)
Clay liners play a critical role in environmental engineering by providing barriers against contaminant migration in containment facilities like landfills. However, challenges persist in optimizing their efficiency, especially in heterogeneous soil conditions. Compaction practices during construction significantly influence clay liner performance, making it imperative to achieve optimal compaction. This study centers on assessing the compaction behavior of composite material comprising marine clay and pressmud, with the goal of advancing sustainable waste containment practices. The plasticity index and liquid limit values of the marine clay are recorded as 37.44% and 62.4%, respectively, indicating High Plasticity Clay (CH). Pressmud, with Atterberg limits including a liquid limit (LL) of 36.5%, plastic limit (PL) of 18.44%, and plasticity index (PI) of 18.06%, is categorized as having medium plasticity. Results reveal that the optimal inclusion of pressmud in marine clay at 10% enhances compaction characteristics, thereby improving load-bearing capacity. The 10% pressmud sample demonstrates the lowest air voids, signifying effective compaction. Therefore, pressmud can contribute to enhance the clay liner in landfill.